Demographic, Clinicopathological Characteristics, and Prognosis of 81 Chinese Elderly Patients With Acral Melanoma - Kaidi Yang; Xin Cai; Jin Wu; Kui Jiang; Weizhen Zhang; Hongfeng Zhou; Fang Liu; Yan Wang; Jiwei Liu; Di Wu (Cancer Medicine, 2026)
ABSTRACT Purpose Acral melanoma (AM) is a rare melanoma subtype involving palms, soles, and nail beds. Clinical‐pathological features and survival of elderly AM patients remain insufficiently understood. This study aimed to investigate the characteristics and survival of elderly Chinese AM patients to support clinical management. Methods Consecutive AM patients aged ≥ 75 years treated at five Chinese melanoma centers between January 2012 and March 2025 were enrolled. Results A total of 81 elderly AM patients were included, with median follow‐up of 76.0 months and median age of 78 years (55.6% male). Most tumors were located on the sole (80.2%). Stage distribution: I 11.1%, II 49.4%, III 19.8%, IV 8.9%. Median overall survival (OS) was 45.0 months, with 1‐, 3‐, 5‐year OS rates of 88.5%, 60.3%, and 36.5%. Univariate analysis showed that high mitotic rate, ulceration, and advanced stage correlated with shorter OS. Multivariate analysis found no independent predictors for OS. Among 72 surgically treated patients, median disease‐free survival (DFS) was 111.0 months, with 1‐, 3‐, 5‐year DFS rates of 76.9%, 63.2%, and 59.9%. Gender was the independent predictor for DFS. Conclusion Multiple clinical‐pathological factors affect the prognosis of elderly AM patients. Male sex is an independent predictor of poor DFS. However, due to the limited sample size for endpoint events, this conclusion has certain limitations. These results provide evidence for the clinical management of elderly AM patients.